MIGA's Financial Sector Guarantees in a Strategic Context - Independent Evaluation Group (Washington, DC: World Bank Group, 2015)
The aim of this report is to inform the design and the implementation of Multilateral Investment Guarantee Agency (MIGA's) new Strategic Directions FY12-14 by drawing lessons from recent experience with one of the main pillars of the MIGA, financial sector guarantees, the fastest growing business area for MIGA. The report presents a forward-looking analysis aimed to inform the development and implementation of MIGA's new strategic direction framework for FY12-14. It looks at the implementation of the current strategy, Operational Directions FY09-11, and assesses performance over the strategy period with respect to its Key Performance Indicators (KPIs) and other indicators. It also includes an updated assessment of MIGA's institutional and operational effectiveness in those areas that are most relevant to strategy implementation.